HEMATOLOGY OF Osphronemus goramy FED CONTAINING FERMENTED TURI (Sesbania grandiflora) LEAF MEAL and CHALLENGED WITH Aeromonas hydrophila - Wahyono, Hendri; Luksityowati, Iesje; Riauwaty, Morina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Turi leaf (Sesbania grandiflora) is a natural ingredient with antibacterial compounds. This research was conducted from April to June 2022 at the Fish Nutrition Laboratory and the Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine, Universitas Riau. This study aimed to obtain the best dose of fermented turi leaves in feed seen from hematology before and after the challenge test with A.hydrophila. The method used in this study is an experimental method using a one-factor Completely Randomised Design (CRD) with five treatment levels, namely Kn: (no treatment), Kp: (no cure and infected with A.hydrophila), P1: (fermented feed containing 15% turi leaves, 85% soy flour), P2: (30% turi leaves, 70% soy flour), and P3: (45% turi leaves, 55% soy flour). Fish were reared for 46 days. The challenge test was conducted on day 32 with A.hydrophila bacteria at a density of 108 CFU/mL, as much as 0.1 mL/head. The results showed that fermented feed contained 45% turi leaves and 55% soybeans (P3). Wheat flour obtained total erythrocytes 2.51x106 cells/mm3, hematocrit 40.33%, hemoglobin 10.40 g/dL, total leukocytes 10.13x104 cells/mm3, phagocytosis activity 21.13%, survival rate 90%, and absolute weight growth 9.52g. Water quality parameters were temperature ranging from 27-300C, pH 5.9-6.2, DO 5.5-5.9 mg/L, and NH3 0.015-0.017 m g/L. Based on the results of the study, it can be concluded that there is an effect of adding fermented turi leaves to feed on the hematology of gouramy before and after the A.hydrophila bacterial challenge test has a significant impact.